Some indivisibility properties of generalized left-factorials - Kohnen, Winfried (Taehan-Suhakhoe-hoebo, 2018)
We shall prove certain p-indivisibility properties of so-called generalized left-factorials, where p is a prime.
Gesehen am 08.02.2019